2020
DOI: 10.1038/s41598-020-66369-z
|View full text |Cite
|
Sign up to set email alerts
|

High Oscillospira abundance indicates constipation and low BMI in the Guangdong Gut Microbiome Project

Abstract: Oscillospira is a common yet rarely cultivated gut bacterial genus. Recently human gut microbiota studies have demonstrated its underlying significance for host health. However, little is known about Oscillospira-related host information and the links between Oscillospira and other members of the gut microbial community. To study the ecology of Oscillospira and gain insights into Oscillospira-related host physiological conditions, we analyzed data from the Guangdong Gut Microbiome Project, one of the largest g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 42 publications
4
72
2
Order By: Relevance
“…Using a zero-inflated beta regression (ZIBR) model (Chen and Li, 2016) to identify differences in abundance or presence of taxa between clusters over time (Table S7) revealed greater prevalence of Coprococcus, Ruminococcus, Oscillospira, and Anaerostipes in the "lowinflammation i" compared to the "high-inflammation" cluster during the high-fiber diet intervention ( Figure 4E). Coprococcus has been associated with higher quality of life indicators and both Ruminococcus and Oscillospira have been associated with improved markers of health including leanness and improved lipid profile (Valles-Colomer et al, 2019;Klimenko et al, 2018;Chen et al, 2020). Anaerostipes had a significant joint p-value in the ZIBR model (Table S7) and was previously described as a "hyper-butyrate producer" (2014).…”
Section: Resultsmentioning
confidence: 84%
“…Using a zero-inflated beta regression (ZIBR) model (Chen and Li, 2016) to identify differences in abundance or presence of taxa between clusters over time (Table S7) revealed greater prevalence of Coprococcus, Ruminococcus, Oscillospira, and Anaerostipes in the "lowinflammation i" compared to the "high-inflammation" cluster during the high-fiber diet intervention ( Figure 4E). Coprococcus has been associated with higher quality of life indicators and both Ruminococcus and Oscillospira have been associated with improved markers of health including leanness and improved lipid profile (Valles-Colomer et al, 2019;Klimenko et al, 2018;Chen et al, 2020). Anaerostipes had a significant joint p-value in the ZIBR model (Table S7) and was previously described as a "hyper-butyrate producer" (2014).…”
Section: Resultsmentioning
confidence: 84%
“…It has been reported that Oscillospira is closely related to human health because its abundance is negatively correlated with systolic and diastolic blood pressure, fasting blood glucose, triglyceride, uric acid, and Bristol scale, suggesting that Oscillospira is a predictor of low BMI and constipation [ 27 ]. In addition, an association between Turicibacter and exercise has been reported in mice.…”
Section: Discussionmentioning
confidence: 99%
“…CR significantly reduced the abundance of Parabacteriodes in old mice potentially reducing inflammation and susceptibility to infections. Similarly, age increased the abundance of the Oscillospira genus and Mucispirillum schaedleri both of which are associated with bowel diseases (Chen et al, 2020;Krych et al, 2015;Toit, 2019), and CR significantly reduced their abundance. On the other hand, age decreased the overall abundance of the Bacteriodes genus and Bacteriodes acidifaciens, and CR increased these in both the cecum and colon of C57BL/6JN mice.…”
Section: Discussionmentioning
confidence: 94%